Voltage-dependent dielectric organic semiconductor polyaniline by Yakuphanoglu dielectric method - Dere, Aysegul; Demirelli, Kadir; Yalcin, Mesut; Mansour, Shehab A.; Yakuphanoğlu, Fahrettin (Elsevier, 2026)
Nanostructured polyaniline (PANI) was prepared by in-situ oxidative polymerisation of aniline using ammonium persulfate as oxidant. The synthesized nanostructured polyaniline was investigated by spectroscopic, morphological, electrical and dielectric methods. The nanostructured polyaniline was confirmed by FT-IR, XRD and SEM analyzes. The dielectric properties such as dielectric constant, dielectric loss, dielectric loss factor, AC conductivity, impedance, admittance and Cole-Cole plots for nanostructured polyaniline were analyzed as a function of frequency between 0.1 V and 5.0 V and at room temperature. Nanostructured PANI was found to change the direction of the phase angle above 2 V and after about 2 kHz. The voltage applied to nanostructured polyaniline was found to have an effect on the electrical and dielectric properties. The increase in the dielectric constant measured at room temperature with increasing voltage facilitates the orientation of electrons and increases the polarization associated with the movement of electrons. The dielectric parameters of nanostructured PANI showed that they can be controlled by an applied DC voltage. In this respect, nanostructured PANI is a voltagedependent dielectric (VDD) material and can be significantly utilized in dielectric applications for capacitors.
Keywords: Polyaniline; Organic semiconductor; Nanostructure; Dielectric material